Importance-Perfomance Analysis (IPA) Implementation: Preference Analysis of Young Consumers of PengenKopi: Case Study on Young Consumer’s of Pengenkopi in Batam City - Chandra, Rio (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
This study aims to analyze the attributes that are considered important by young consumerswhen they are going to buy in Pengkopi Coffee Shop, attributes that are considered to have goodperformance by consumers and also attributes that are considered appropriate between the interests andperformance of young consumers when they will buy coffee. The type of research in this research isdescriptive quantitative research. The descriptive method begins by collecting data from the field whichaims to get an overview and explanation of the phenomena of events that occur today. This research islocated in the Coffee Shop or Coffee Shop Pengkopi in Batam City, Riau Islands which is the location fordistributing research questionnaires widely. The sampling technique used is non-probability sampling withthe technique taken is purposive sampling. The sample in this study were 200 respondents, namelyconsumers from Pengkopi Batam who had come directly to coffee shops. The analysis of this research iscarried out by means of performance-interest analysis (IPA) to rankvarious service attributes and identifywhat actions the company needs to take. The results show that the attributes that are considered veryimportant by consumers when they will make a purchase of Coffee Shop are attributes of coffee taste, coffeeprices, coffee flavor variants, physical coffee menus, menu presentation, convenience, menu size/volume,information and service menu. Meanwhile, the important category according to the respondents is thebenefits of coffee in Pengkopi. Attributes that are considered to have very good performance by consumerswhen they are going to make a purchase of coffee at Pengkopi are the taste of coffee, coffee prices, physicalappearance , comfort , size/volume, menu information and services at Pengkopi. Meanwhile, those that arecategorized as good or satisfied are the taste variants, the benefits of coffee and the presentation of themenu at the Coffee Shop. Attributes that are considered appropriate between the interests and performanceof consumers when they are going to make a purchase of coffee at the Kopi are the services provided by theCoffee Maker.